Occurrence of jasmonates during cystocarp development in the red alga Grateloupia imbricata. Issue 6 (28th October 2016) - Pilar, Garcia‐Jimenez; Olegario, Brito‐Romano; Rafael, Robaina R.
Abstract : In this study, we highlight the effects of methyl jasmonate (MeJa) on cystocarp development in the red macroscopic alga Grateloupia imbricata . In G. imbricata, jasmonate release is related to the reproductive state, as fertile thalli (i.e., those that have cystocarps) released significant amounts of this volatile compound (1.27 ± 0.20 mM · mg fw −1 · h −1 ) compared with infertile thalli (0.95 ± 0.12 mM · mg fw −1 · h −1 ). Treating G. imbricata thalli with MeJa revealed a significant increase in cystocarp number (1.5 ± 0.27 cystocarps · mm −2 ), which was 7.5‐fold greater than in untreated thalli (0.2 ± 0.07 cystocarps · mm −2 ). Maturation was completed within 48 h with MeJa treatment, a shortening of the typical >3‐week maturation period, and included the opening of cystocarps and the presence of dehiscent cavities. Release rates of jasmonates after exogenous MeJa treatment were also modified based on the cystocarp maturation level. All of these effects were reduced in the presence of phenidone, which blocks MeJa production, indicating that the MeJa action is genuine. The effects of MeJa during cystocarp maturation were not replicated by derivatives of reactive oxygen species from the same jasmonic acid biosynthetic pathway, as the activities of scavenger enzymes and lipid peroxidation were unchanged between infertile and fertile thalli. Therefore, a reactive oxygen species–based mechanism is not involved during cystocarp development. We conclude that MeJa has an independent function as a growth regulator during G. imbricata reproduction.